2013
DOI: 10.1002/rra.2718
|View full text |Cite
|
Sign up to set email alerts
|

Flow Analysis of a River Confluence with Field Measurements and Rans Model with Nested Grid Approach

Abstract: A comprehensive flow analysis for a confluence of two medium‐sized (Qmean ≈ 30–50 m3/s) Hungarian rivers was carried out by means of a three‐dimensional Reynolds‐averaged Navier–Stokes modelling. The model was validated against detailed fixed and moving Acoustic Doppler Current Profiler velocity profiling. Unsteady simulations with steady‐state boundary conditions were performed on a structured grid in order to reveal the characteristic large‐scale spatial behaviour of the flow, such as strong secondary curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The computational hydrodynamic model used in this research (Olsen, 2010) had already been tested and validated in many riverine flow and sediment transport studies. These applications focused on FIGURE 2 Grain size distribution curves of the bed material samples (the sampling locations of Samples 1-4 are indicated in Figure 1b) the analysis of hydraulic structures (e.g., Haun, Olsen, & Feurich, 2011;Olsen & Kjellesvig, 1998); simulation of reservoir flushing (e.g., Haun & Olsen, 2012;Olsen, Jimenez, Abrahamsen, & Løvoll, 1999); laboratory scale simulations (e.g., Baranya & Józsa, 2007;Baranya, Olsen, Stoesser, & Sturm, 2012;Ruether & Olsen, 2005); river flow simulations (e.g., Baranya & Józsa, 2006;Olsen & Stokseth, 1995;Wilson, Yagci, Rauch, & Olsen, 2006); simulation of mixing in rivers (e.g., Baranya, Olsen, & Józsa, 2015); and simulation of river morphodynamics (e.g., Baranya, 2010;Fischer-Antze, Olsen, & Gutknecht, 2008). The numerical model solves the so-called Reynolds-averaged Navier-Stokes equations on a horizontally structured, curvilinear grid system.…”
Section: Computational Modelling and Bed Materials Mappingmentioning
confidence: 99%
“…The computational hydrodynamic model used in this research (Olsen, 2010) had already been tested and validated in many riverine flow and sediment transport studies. These applications focused on FIGURE 2 Grain size distribution curves of the bed material samples (the sampling locations of Samples 1-4 are indicated in Figure 1b) the analysis of hydraulic structures (e.g., Haun, Olsen, & Feurich, 2011;Olsen & Kjellesvig, 1998); simulation of reservoir flushing (e.g., Haun & Olsen, 2012;Olsen, Jimenez, Abrahamsen, & Løvoll, 1999); laboratory scale simulations (e.g., Baranya & Józsa, 2007;Baranya, Olsen, Stoesser, & Sturm, 2012;Ruether & Olsen, 2005); river flow simulations (e.g., Baranya & Józsa, 2006;Olsen & Stokseth, 1995;Wilson, Yagci, Rauch, & Olsen, 2006); simulation of mixing in rivers (e.g., Baranya, Olsen, & Józsa, 2015); and simulation of river morphodynamics (e.g., Baranya, 2010;Fischer-Antze, Olsen, & Gutknecht, 2008). The numerical model solves the so-called Reynolds-averaged Navier-Stokes equations on a horizontally structured, curvilinear grid system.…”
Section: Computational Modelling and Bed Materials Mappingmentioning
confidence: 99%
“…CFD models simulate effectively fluvial settings characterized by high hydrodynamic complexity [29,30]. For instance, Baranya et al [31] used CFD for simulating confluences of two medium-sized Hungarian rivers through a 3D Reynolds-averaged Navier-Stokes (RANS) model.…”
Section: Computational Fluid Dynamics Models In the Framework Of Curvmentioning
confidence: 99%
“…Yang (2013) used a numerical model with a dynamic meshwork to investigate the flow characteristics in a 90° junction; the comparison between the model and experimental results revealed that the model is highly capable of predicting the water level and velocity values. Baranya et al (2013), by means of a 3-dimensional Reynolds-averaged Navier-Stokes model, carried out a comprehensive flow analysis for a confluence of 2 medium-sized Hungarian rivers. They converted a nested grid into a coarse grid to simulate unsteady vortex shading.…”
Section: Figurementioning
confidence: 99%
“…The use of numerical models for simulating the flow in river junctions has recently attracted researchers' attention, such as Weerakoon et al (1991), Huang et al (2002), Biron et al (2004) and Chen and Peng (2006). Weerakoon et al (1991) used a fully elliptic treatment in study of a 60° asymmetrical confluence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation